Impact of hepatitis C viremia on overall survival and hepatic decompensation among patients with unresectable HCC receiving immunotherapy - Eunice Y. Lee; Willis Tang; Jennifer C. Price; Robin K. Kelley; John D. Gordan; Jennifer C. Lai; Lawrence Fong; Neil Mehta; Michael Li (Clinical and Translational Gastroenterology, 2026)
Introduction: Hepatitis C (HCV) is associated with an immunosuppressive liver microenvironment, but whether HCV affects immune checkpoint inhibitor (ICI) outcomes in unresectable hepatocellular carcinoma (HCC) remains unknown. Methods: We performed a single-center retrospective cohort study of patients with unresectable HCC treated with ICIs. In patients with a history of HCV, viremia was defined as a detectable viral load prior to immunotherapy. The primary outcome was overall survival (OS); secondary outcomes were real-world progression-free survival (PFS), time on treatment, and time to hepatic decompensation. Results: Among 350 unresectable HCC patients treated with ICIs, 135 (39%) had a history of HCV, of which 37 (27%) were viremic. Viremia was not associated with OS (HR 0.88, 95% CI 0.53-1.44, p=0.600), but was associated with longer real-world PFS (HR 0.59, 95% CI 0.36-0.96, p=0.033) and longer time on treatment (HR 0.63, 95% CI 0.40-0.99, p=0.044). Compared to patients with non-HCV related unresectable HCC (n=215), viremic patients had longer real-world PFS (HR 0.65, 95% CI 0.44-0.97, p=0.037) but non-viremic patients did not (HR 0.87, 95% CI 0.66-1.17, p=0.359). Viremia was not associated with time to hepatic decompensation (HR 1.11, 95% CI 0.61-2.04, p=0.728), but in patients who survived at least one year without decompensating, viremia was associated with shorter time to decompensation (29.8 months vs. median not reached, log-rank p=0.010). Conclusions: Viremia was not associated with OS among ICI-treated HCV patients with unresectable HCC, but was associated with longer real-world PFS and time on treatment. Further studies are needed to investigate these findings.